Relationship between diagnostic characteristics, lifestyle habits and breast cancer subtypes in women - Fernanda Cristina Marin; Clóvis Arlindo de Sousa; Erika de Sá Vieira Abuchaim; Isília Aparecida Silva (Revista Latino-Americana de Enfermagem)
Objective: to investigate the relationship between diagnostic characteristics, lifestyle, habits and the occurrence of breast cancer subtypes in adult and elderly women. Method: cross-sectional study of women over 18 years old undergoing treatment or follow-up for breast cancer at a cancer institute in the state of São Paulo. Data were collected between December 2022 and July 2023 through telephone interviews and a survey of electronic medical records. Statistical analysis included absolute and relative frequency distribution and bivariate analysis, using the Chi-square test or Fisher’s Exact Test, considering statistically significant values with p≤0.05, with a 95% confidence interval. Results: 323 women took part in the study. Women who did not consume processed foods, soft drinks, or artificial juices had a lower proportion of ductal carcinoma. And those aged <40 had a higher proportion of the triple negative breast cancer subtype. Conclusion: the results indicate a significant relationship between age at diagnosis and molecular subtype, as well as relevant patterns between the consumption of industrialized foods and soft drinks or artificial juices and the histological subtypes of the disease. These findings highlight the importance of considering such factors in the prevention of the disease.